2020
DOI: 10.21203/rs.3.rs-53958/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircSOD2 induced epigenetic alteration drives hepatocellular carcinoma progression through activating JAK2/STAT3 signaling pathway

Abstract: Background:Emerging evidence suggests that circular RNAs play critical roles in disease development especially in cancers. Previous genome-wide RNA-seq studies found that a circular RNA derived from SOD2 gene was highly upregulated in hepatocellular carcinoma (HCC), however, the role of circSOD2 in HCC remains largely unknown. Methods: The expression profiling of circSOD2 and microRNA in HCC patients were assessed by Real-Time Quantitative Reverse Transcription PCR (qRT-PCR). SiRNA or CRISPR-CAS9 were used to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…For example, circHIPK3 acts as a tumor-suppressive function in ovarian cancer [28]. Via activating JAK2/STAT3 signaling pathway, hepatocellular carcinoma progression was driven by circSOD2 induced epigenetic alteration [29] Circ-0000284 modulates the biological functions of peripheral cells via cellular communication and arouses malignant phenotype of CCA cells [30]. In this study, we observed circ-0006302 expression levels in CCA tissues are distinctly higher than that in non-tumorous tissues.…”
Section: Discussionmentioning
confidence: 63%
“…For example, circHIPK3 acts as a tumor-suppressive function in ovarian cancer [28]. Via activating JAK2/STAT3 signaling pathway, hepatocellular carcinoma progression was driven by circSOD2 induced epigenetic alteration [29] Circ-0000284 modulates the biological functions of peripheral cells via cellular communication and arouses malignant phenotype of CCA cells [30]. In this study, we observed circ-0006302 expression levels in CCA tissues are distinctly higher than that in non-tumorous tissues.…”
Section: Discussionmentioning
confidence: 63%
“…Increased IL-6 leads to IL-6 receptor activation, which then activates IL-6-related cell signaling pathways, especially IL-6/JAK2/STAT3 pathway 46 . According to most current studies, aberrant activation of JAK2/STAT3 signaling pathway promotes disease progression and is detrimental to the control of diseases, including liver cancer 47 , in ammation 48 and neurological disease 49 . In our study, it was observed that the expressions of IL-6, p-JAK2, and p-STAT3 were abnormal up-regulated in HGFs after LPS induction, and the effect of LPS stimulation was partially reversed following transfection with miR-655-3p mimics.…”
Section: Discussionmentioning
confidence: 99%
“…17 CircSOD2 contributed to the HCC progression by targeting the miR-502-5p/ DNMT3a axis to activate the JAK2/STAT3 pathway. 18 Also, GL63 has suppressed cell proliferation by blocking the JAK2/STAT3 signaling pathway in HCC cells. 7 This study concentrated on the anti-tumor mechanism of GL63 in HCC.…”
Section: Introductionmentioning
confidence: 99%